Civic Pride and Political Devotion: The Relics of Thomas Becket in Siena - Mazzocchio, Cecilia (Religions, 2022)
Through a survey of archival and primary source material, this article discusses the existence of St. Thomas Becket’s relics in Siena cathedral. The institution’s inventories indicate that, from 1482 until ca. 1529, the relics were housed in an ostensory kept in the sacristy. Today, this object is displayed in the Sala del Tesoro, in the Museum of the Opera del Duomo in Siena. Although the ostensory has been examined in previous scholarship concerned with mapping the cathedral’s heritage, its function as a vessel for the relics of Thomas Becket, and indeed the very presence of these relics in Siena, remain unexplored. Thus, seeking to understand the nature of Becket’s reception in Siena, I examine the whereabouts of his relics within the cathedral, to then widen the investigation to the city at large. The evidence shows that although there were no chapels, altars or churches dedicated to Thomas Becket within the city walls, Siena still engaged with Becket’s sainthood and legacy on multiple levels.